Penggunaan Stiker Keselamatan dan Kesehatan Kerja (K3) sebagai Upaya Pencegahan Kecelakaan Kerja di Biro SDM Polda Kalimantan Selatan - Wahdati, Anisya; Yanti, Risda; Komalasari, Shanty; Musfichin (Fakultas Psikologi Universitas Pancasila, 2022)
The decline in occupational safety and health is a problem that occurs in the world of work. The number of work accidents that occur especially for employees who work in an environment that has a high risk of health and safety. Occupational safety and health in an organization is not only influenced by the system that has been implemented by the organization, but is also implemented by everyone's awareness of how to prevent it. The number of work accidents caused by a lack of knowledge about occupational safety and health (K3) and a non-conducive work environment. To overcome this problem, it is necessary to use K3 stickers in the work environment to prevent work accidents, especially in the Human Resources Bureau of the South Kalimantan Police. The purpose of holding this community service activity is to introduce the importance of occupational safety and health (K3) in the organization so that the staff of the South Kalimantan Police HR Bureau are aware of the importance of occupational safety and health (K3). The results of community service (PKM), concluded that the sticking of K3 stickers in the work room made the staff take the initiative to remove the power plug after use. Unlike before this PKM activity, many electrical plugs were found in the workspace that were still installed and not removed after use. Through this PKM activity, it is hoped that it will have a beneficial effect and educate the staff of the HR Bureau to always be careful about work safety.